Người anh hùng áo trắng - Nguyễn Hoài Thu, Trần Ngọc Thanh; Trần Ngọc Thanh (H. Nxb. Thanh Niên, 1986)
Cuộc đời và sự nghiệp của bác sĩ, anh hùng Phạm Ngọc Thạch
Keywords: cuộc đời; Phạm Ngọc Thạch; Y tế